The Long and the Short of it: the Role of Short-course Radiotherapy in the Neoadjuvant Management of Rectal Cancer. Issue 5 (May 2022) - Slevin, F.; Hanna, C.R.; Appelt, A.; Cunningham, C.; Marijnen, C.A.M.; Sebag-Montefiore, D.; Muirhead, R.
Abstract: Total mesorectal excision is the cornerstone of treatment for rectal cancer. Multiple randomised trials have shown a reduction in local recurrence rates with the addition of preoperative radiotherapy, either as a 1-week hypofractionated short-course (SCRT) or a conventionally fractionated long-course (LCRT) schedule with concurrent chemotherapy. There is also increasing interest in the addition of neoadjuvant chemotherapy to radiotherapy with the aim of improving disease-free survival. The relative use of SCRT and LCRT varies considerably across the world. This is reflected in, and is probably driven in part by, disparity between international guideline recommendations. In addition, different approaches to treatment may exist both between and within countries, with variation related to patient, disease and treatment centre and financial factors. In this review, we will specifically focus on the use of SCRT for the treatment of rectal cancer. We will discuss the literature base and current guidelines, highlighting the challenges and controversies in clinical application of this evidence. We will also discuss potential future applications of SCRT, including its role in optimisation and intensification of treatment for rectal cancer.